The Role of Green Marketing in Driving Consumer Preferences for Sustainable Products in E-Commerce - Manna, Yahya (International Review of Management and Marketing, 2025)
With increasing consumer demand for sustainable products, e-commerce platforms are integrating green marketing initiatives to attract consumers. In recent years, consumer preferences for sustainable products have experienced significant growth, driven in part by increased consciousness among consumers for green products. In this regard green marketing initiatives has a role in influencing consumer decisions for sustainable products in the e-commerce sector. Green marketing is a promotion of environmentally friendly products, is not only a strategic business tool but also a critical component in encouraging sustainable consumption patterns. The study investigates the mechanisms through which green marketing initiatives can shift consumer attitudes and behaviours in favour of sustainable products in online marketplaces. By analysing data from 501 respondents, this research highlights how e-commerce platforms leverage green marketing techniques to cater to environmentally conscious shoppers. This study employs structural equation modelling (SEM) to analyse green marketing initiatives, brand trust, perceived value and purchase intentions in e-commerce context. The paper explores the relationships between green marketing initiatives (such as eco-labelling, sustainable branding, transparency, and product sustainability) and key consumer outcomes (such as trust, perceived value, and purchase intention). The SEM analysis reveals that green marketing significantly influences consumer attitudes and purchase behaviour, with perceived product sustainability and brand trust emerging as the most impactful mediators. This research provides actionable insights for e-commerce businesses aiming to leverage green marketing to attract and retain eco-conscious consumers.